Analysis of human lung mast cells by single cell RNA sequencing - Rönnberg, Elin; Ravindran, Avinash; Mazzurana, Luca; Gong, Yitao; Säfholm, Jesper; Lorent, Julie; Dethlefsen, Olga; Orre, Ann-Charlotte; Al-Ameri, Mamdoh; Adner, Mikael; Dahlén, Sven-Erik; Dahlin, Joakim S.; et al. (Frontiers in Immunology, 2023)
Mast cells are tissue-resident cells playing major roles in homeostasis and disease conditions. Lung mast cells are particularly important in airway inflammatory diseases such as asthma. Human mast cells are classically divided into the subsets MCT and MCTC, where MCT express the mast cell protease tryptase and MCTC in addition express chymase, carboxypeptidase A3 (CPA3) and cathepsin G. Apart from the disctintion of the MCT and MCTC subsets, little is known about the heterogeniety of human lung mast cells and a deep analysis of their heterogeniety has previously not been performed. We therefore performed single cell RNA sequencing on sorted human lung mast cells using SmartSeq2. The mast cells showed high expression of classical mast cell markers. The expression of several individual genes varied considerably among the cells, however, no subpopulations were detected by unbiased clustering. Variable genes included the protease-encoding transcripts CMA1 (chymase) and CTSG (cathepsin G). Human lung mast cells are predominantaly of the MCT subset and consistent with this, the expression of CMA1 was only detectable in a small proportion of the cells, and correlated moderately to CTSG. However, in contrast to established data for the protein, CPA3 mRNA was high in all cells and the correlation of CPA3 to CMA1 was weak.